DEVELOPMENT STRATEGY OF FOOTWEAR SMEs - Putri, Revina Devitani; Hubeis, Musa; Syamsun, Muhammad (Jurnal Aplikasi Manajemen, 2017)
Kabupaten Bogor is a city which potentialy produce footwear. Data from Bogor Regency Department of Industry and Trade of year 2011 shows that there are 4.178 enterprises units which accommodate 15.295 labors and it has currency gyrations Rp5 billion per day. Ciomas District is one of footwear Small and Medium Enterprises (SMEs atau UKM) centers located at Bogor Regency.The purposes of this study are: (1) Identify the footwear SMEs characteristics at Ciomas Bogor Regency; (2) Analyze the internal and external environment of the UKM at Ciomas Bogor Regency; (3) Arrange the UKM development strategy at Ciomas Bogor Regency.Purposive sampling is used for the determination of respondents. Data processing and analysis in this study conducted by descriptive, quantitative, and qualitative. Matrix Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), position strategy, Strengths, weaknesses, Opportunities and Threats (SWOT), and Analitical Hierarchy Process (AHP) are used to analyze the quantitative data. IFE matrix score -0,30 and EFE matrix score 0,33. It means that strategic position of footwear SMEsCiomas at Kuadran III which we can say that footwear SMEs has big and vast opportunities but also it has weakness. The priorityalternative strategy for footwear SMEs development are: production increase, expand market shareand adopt advanced technology.